Вплив метаболічного синдрому на перебіг раку молочної залози - Щепотін, І. Б.; Зотов, О. С.; Любота, І. І.; Любота, Р. В. (Clinical Endocrinology and Endocrine Surgery, 2011)
A total of 100 patients aged 27 to 82 years (56±12) who underwent treatment for breast cancer (BC) in clinical of oncology department of the National Medical University named after AA Bogomolets on the basis of the surgical department of the Kyiv City Oncology Hospital in 2008. Patients were divided into two groups – experimental and control. In the experimental group was the 64 women who have breast cancer diagnosed and the metabolic syndrome (MS), and in the control group – 36 women, breast cancer patients without the metabolic syndrome. Found that the presence of MS in patients associated with bad prognosis of breast cancer.